2018
DOI: 10.1210/jc.2018-01159
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-Pituitary-Testicular Axis Effects and Urinary Detection Following Clomiphene Administration in Males

Abstract: Context Clomiphene is a performance-enhancing drug commonly abused by males in sport, but the extent to which testosterone increases in healthy males following its use is unknown. In addition, evidence suggests that clomiphene, a mixture of cis- and trans-isomers zuclomiphene and enclomiphene, is detectable in urine for months following use; the isomer-specific urinary detection window has yet to be characterized in a controlled study. Objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…In agreement with earlier findings 41–43 in 77% of the samples where the metabolite was identified, LGD4033 was not detectable at all. On the contrary, cis‐clomiphene was often detected alone or present in much higher concentration than 4‐hydroxyclomiphene, corroborating observations of Guddat et al 44 and Miller et al 45 Only one sample was found to contain 4‐hydroxyclomiphene in the absence of parent drug, which may be ascribed to administration of enclomiphene 46,47 …”
Section: Resultssupporting
confidence: 81%
“…In agreement with earlier findings 41–43 in 77% of the samples where the metabolite was identified, LGD4033 was not detectable at all. On the contrary, cis‐clomiphene was often detected alone or present in much higher concentration than 4‐hydroxyclomiphene, corroborating observations of Guddat et al 44 and Miller et al 45 Only one sample was found to contain 4‐hydroxyclomiphene in the absence of parent drug, which may be ascribed to administration of enclomiphene 46,47 …”
Section: Resultssupporting
confidence: 81%
“…Clomiphene has been shown to increase testosterone by 150% for multiple weeks after use, and it also increases two other types of androgens, epitestosterone, and 4androstenedione (3,14). These effects are mostly seen in males while females show a smaller effect, because most female androgens are made by non-gonadal organs, and these productions are independent of pituitary hormones (14).…”
Section: Discussionmentioning
confidence: 99%
“…Clomiphene has several markers and metabolites which can be found in urine; 4-hydroxyclomiphene and 3-methoxy-4hydroxyclomiphene being the most common metabolites being tested in doping labs as well as clomiphene isomers, namely Zuclomiphene and Enclomiphene (3,15,16). In a study in 2019, Miller et al showed that Zuclomiphene can be found in urine for an average of 98 days and, in some cases, up to 8 months after the final dose of clomiphene (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, clomiphene citrate, an estrogen receptor regulator, increases the secretion of GnRH in the hypothalamus by inhibiting the negative feedback regulation of estrogen. In addition to treating female ovulation dysfunction, clomiphene citrate also improves the levels of testosterone and GnRH in men (155)(156)(157). Aromatase inhibitors, which are estrogen receptor regulators, promote the release of GnRH by modulating estrogen levels.…”
Section: Effects Of Lh On Reproductive Developmentmentioning
confidence: 99%